2020
DOI: 10.21315/kajh2020.27.1.5
|View full text |Cite
|
Sign up to set email alerts
|

South Korean Media Representation of Yemeni Refugees

Abstract: This research examines how a handful of Yemeni refugees who arrived in South Korea are depicted in the online media news reports of the country. A total of 73 articles were collected from five different Korean English news outlets. The representation of social actor theory and conceptual metaphor theory were used in the analysis of the data. The outcomes of the analysis indicate that these Yemeni refugees are undesirably represented by the South Korean media. The continuance of such undesirable representation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…humanitarian in nature highlighting their suffering and urging the international community to empower them. This is inconsistent with Abid (2020) who found that refugees were negatively and undesirably portrayed in the media outlets of some host communities.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…humanitarian in nature highlighting their suffering and urging the international community to empower them. This is inconsistent with Abid (2020) who found that refugees were negatively and undesirably portrayed in the media outlets of some host communities.…”
Section: Discussioncontrasting
confidence: 74%
“…Several scholars have carried out different research studies about the status of females in general and female refugees in particular. Some of the studies discussed the representation of women in media (Abid, 2020;Ghazal Aswad, 2019;Haider & Olimy, 2019;Mustafa-Awad et al, 2019;Mustafa-Awad & Kirner-Ludwig, 2017;Narlı et al, 2020;Narlı & Özaşçılar, 2019). However, most of these studies did not pay considerable attention to how female refugees are stereotyped in national news agencies that publish mainly in Arabic.…”
Section: Research-article20212021mentioning
confidence: 99%
See 2 more Smart Citations